Etude par simulation du transfert de chaleur dans une plaque conductrice - CHAIB HICHAM; OUAR MOHAMMED ABDELATIF; Yousfi, Belkacem (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2024)
In this work, we measured the evolution of heating by the Joule effect, electrical conductivity, total current density, temperature, heat flow in terms of different resistivity values, We supported this research by student using the COMSOL simulation unit to obtain results, It is very important to confirm the extent of the role of resistivity in the heat transfer results, because we conclude that the higher the value of the resistance is lower, the higher the value of the physical parameters.
MAINTENANCE INDUSTRIELLE